Expert System Diagnosing Gastric Disease Using Hybrid Method - Yenila, Firna; Wahyuni, Suci (Knowbase : International Journal of Knowledge in Database, 2022)
The gastric is a vital organ that must be maintained by maintaining a balanced life. The lack of time to discuss with patients, the causes of stomach disease is frequently overlooked. Need a new way to consult with patients without seeing the time. Expert consul is an application based on knowledge such as an expert system. This research was proposed to provide education to system users who have problems with the stomach. So that treatment can be obtained quickly and the stomach's condition can be better. This research includes a system designed by incorporating an expert's expertise into a system by combining the forward chaining method by describing the conditions experienced by patients in the form of sequential questions and the certainty of factors that provide some of the patient's belief in experiencing these conditions, which are used as desires in decision making. The result of the expert system using the hybrid method obtained consultation results with a 76 % certainty level, indicating that the patient was quite certain of having the disease that was conveyed in accordance with the knowledge that had been adopted by the expert so that the patient received the right therapy early before further consultation with experts.Â Lambung merupakan organ vital yang harus dijaga dengan menjaga hidup seimbang. Singkatnya waktu untuk berdiskusi dengan pasien menyebabkan penyakit lambung sering terabaikan. Dibutuhkan cara baru untuk berkonsultasi dengan pasien tanpa melihat waktu konsultasi pakar berupa sebuah aplikasi berbasis pengetahuan seperti system pakar. Penelitian ini diajukan untuk memberikan edukasi kepada pengguna system yang memiliki masalah dengan lambung berupa informasi persentase menderita penyakit tersebut. Sehingga penanganan cepat didapatkan dan kondisi lambung bisa kembali seperti sediakala. Penelitian ini mengusung aplikasi system pakar yang dirancang dengan menyadurkan kepakaran seorang ahli kedalam sebuah system dengan menggabungkan metode forward chaining dengan memaparkan kondisi yang dialami oleh pasien dalam bentuk pertanyaan secara berurutan dan certainty factor yang memberikan persentase tingkat keyakinan pasien mengalami kondisi tersebut yang dijadikan acuan dalam pengambilan keputusan. Hasil yang didapatkan dalam system pakar yang melakukan pengujian terhadap metode hybrid tersebut didapatkan hasil konsultasi dengan tingkat kepastian 76% yang menyatakan bahwa pasien dinyatakan cukup yakin mengidap penyakit yang disampaikan sesuai dengan pengetahuan yang sudah disadurkan oleh pakar, sehingga pasien mendapatkan terapi yang tepat secara dini sebelum berkonsultasi lanjut dengan pakar.